Professor Tariel Putkaradze on Abkhazia (based on his notes) - Vashakidze, Iamze (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2022)
As a respected scholar and public figure, Tariel Putkaradze has extensively examined the past and the determining factors of the current situation in Abkhazia. Employing both scientific-educational methods and social networks, his research aims to facilitate a proper orientation in the struggle for the restoration of the country΄s conquered territories. This paper summarizes the researcher›s position as recorded in his work, highlighting the following key points: 1. Abkhazia is an integral part of a unified Georgia, affirmed by the unanimous support of the Abkhazian population in the March 31, 1991 referendum. The conflict in Abkhazia is viewed as an element of the broader Russo-Georgian war that began on December 22, 1991. It is seen as a war against the state of Georgia, including the Apsua ethnos, and involving state criminals. Addressing these issues within the political spectrum is crucial for establishing the correct trajectory for the country΄s progress. 2. A differentiated approach is necessary when engaging with the population residing in the occupied territories. While some support the Russian occupiers, others advocate for the restoration of Georgia›s territorial integrity. 3. Overcoming the information warfare targeted against Georgia is of paramount importance. This entails combating falsified history and terminological sabotage, which aim to isolate Georgia from the West and leave it unsupported in the face of the Russian Empire. 4. The path towards reunification of Abkhazia (as well as the Tskhinvali region) lies in achieving real independence for the country through a Western European orientation. Joining the Commonwealth of Nations while preserving its national ethnic identity requires the unity of Georgian citizens in national-state affairs. This unity will enable the consolidation of the peoples of the Caucasus in their struggle for independence. 5. Following de-occupation, Georgia must take effective measures to reclaim the Russian-occupied territories of Abkhazia. This is crucial for the preservation of the Abkhazian ethnos, language, and culture, which are currently under threat of extinction within the Russian imperial sphere. By addressing these issues, Professor Putkaradze contributes valuable insights to the discourse surrounding Abkhazia΄s complex political and social dynamics.